Academic Supervision Management by School Principals in Enhancing Teachers' Social Competence: A Comparative Case Study of Two Elementary Schools - Ani Kania; Eva Dianawati Wasliman (Journal of Innovation and Research in Primary Education, 2026)
Principal academic supervision is an important means of improving teachers' social competence to support effective communication, cooperation, and professional classroom management. This study was motivated by the importance of the principal's role in providing continuous guidance, direction, and evaluation. The purpose of this study is to describe the planning, implementation, evaluation, follow-up, obstacles, and solutions of academic supervision by the principal in improving teachers' social competence at SDN Sintok and SDN Margasari. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation, then analyzed thematically. The results showed that supervision at SDN Sintok emphasized personal assistance, while at SDN Margasari it was carried out in a structured manner with an annual work program. Supervision was proven to improve teachers' communication skills, cooperation, self-confidence, and reflective attitudes. In conclusion, academic supervision plays a strategic role in improving teachers' social competence through planned, flexible, and solution-oriented guidance.